1994
DOI: 10.1159/000110367
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Lacunes and Parkinsonism

Abstract: ''Arteriosclerotic'' parkinsonism is still a subject of debate. The aim of this study was to investigate whether parkinsonism associated with basal ganglia lacunes possesses peculiar clinical features and a clinical course which enables its distinction from idiopathic Parkinson''s disease (IPD). 106 consecutive ambulatory patients with the clinical diagnosis of parkinsonism were referred for CT examination. Patients in whom isolated basal ganglia lacunes were found were interviewed and examined, and their clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 8 publications
2
37
0
1
Order By: Relevance
“…L -Dopa-responsive cases with vascular lesions in the absence of pathological changes in the SNpc [15]and, conversely, L -dopa-unresponsive cases with pathological changes in the SNpc [44]have been reported. Third, IPD symptoms may possibly be modified by a few, small ischemic lesions [21, 45, 46]. A study reported that parkinsonian symptoms did not differ between patients with and without isolated lacunes in the basal ganglia on computed tomography scans except for less frequent tremor in the former [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L -Dopa-responsive cases with vascular lesions in the absence of pathological changes in the SNpc [15]and, conversely, L -dopa-unresponsive cases with pathological changes in the SNpc [44]have been reported. Third, IPD symptoms may possibly be modified by a few, small ischemic lesions [21, 45, 46]. A study reported that parkinsonian symptoms did not differ between patients with and without isolated lacunes in the basal ganglia on computed tomography scans except for less frequent tremor in the former [45].…”
Section: Discussionmentioning
confidence: 99%
“…Third, IPD symptoms may possibly be modified by a few, small ischemic lesions [21, 45, 46]. A study reported that parkinsonian symptoms did not differ between patients with and without isolated lacunes in the basal ganglia on computed tomography scans except for less frequent tremor in the former [45]. In the present study, cases with only a few lacunes were included into the group without significant infarct because much higher sensitivity of MRI compared to computed tomography scans did not allow a clear-cut classification of individual cases into those with or without a few lacunes.…”
Section: Discussionmentioning
confidence: 99%
“…Rest tremor of the upper limbs, that is frequently absent in VaP [7, 25, 28, 29], was present in 7 out of 10 patients. Gait disturbances that are considered to be prominent in VaP [7, 23, 25, 26, 27, 28, 29]were found in all our patients, except in 1.…”
Section: Discussionmentioning
confidence: 99%
“…Forty consecutive patients, admitted to the Neurological Department of the Ghent University Hospital with a diagnosis of ‘probable’ vascular dementia, according to the SCADDTC [46]and the NINDS-AIREN [7]criteria, were studied. All of them had a score of more than 7 points on the Hachinski’s ischemic scale [48].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation